Evaluation of State Vocational School Leadership in North Sulawesi - Tambingon, Henny (International Journal of Psychosocial Rehabilitation, 2020)
Vocational School (VS) is expected to educate students who have competencies in accordance with their fields of expertise. These competencies determine the future of students to apply in their job. The principal of the vocational school has the role of producing graduates who have competencies in accordance with the needs of the industry. The aim of the study was to evaluate the managerial ability of the principal of the State vocational school in the North Sulawesi province. This study used a survey method. The study sample consisted of 36 teachers, each school represented by a teacher. The research data was obtained using interview techniques, then the research data were analyzed using a qualitative approach. The results showed that the ability of principals to lead VS in the province of North Sulawesi was sufficient, but not yet maximal.